Antioxidant Therapy as a Protector and Corrector of Haematological Toxicity of Systemic Therapy for Breast Cancer - Prokhach, A. V.; Bondarenko, I. M.; Kulinich, R. V.; Bukhtiyarova, N. V.; Кулинич, Роман Леонідович; Бухтіярова, Ніна Вікторівна (My University, 2016)
Side effects of anticancer drugs seriously limit the achievement of the maximum therapeutic effect of the most cytostatics. Pathophysiological basis of side effects is the ability of cytotoxic agents to intensify the free-radical processes and the con sequent lipid peroxidation (LPO) in the cell membranes of various organs. In our study we observed the efficacy of antioxidant therapy in the prevention of the development of leukopenia. It was discovered that administration of antioxidant therapy during course of chemotherapy for breast cancer leads to significantly lower incidence of leukopenia (78.5% of cases in control group versus 43.8% in study group with study drug), and lower incidence of deep leukopenia. Also in was found that patients with a low level of SH-groups (less than 1 mmol / g protein) in parallel activation of oxidative stress are in the risk group for the occurrence of neutropenia in the background of breast cancer chemotherapy and require dynamic observation with individual selection of donators thiols and drugs with proven antioxidant effect. Reduction in the activity of antioxidant enzymes of glutathione level and the displacement of the thiol-disulfide equilibrium in the direction of reducing of the content of reduced forms indicates a reliable clinical need for the personal use of drugs with glutathione-protective effect and antioxidant potential.
Keywords: Breast cancer; hematological toxicity; leucopenia; chemotherapy; antioxidant therapy